The Man’s Image in Naz Kakaees poems - کوردستان موکرانی (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
After woman had expressed her dreams, ambitions and struggles of life through poetry and other literary arts, she has transformed from being a literary subject dealt by poets for many poetic purposes to human contributes in regulating poetry and that proves her active involvement in building up the literary project. The research aims to reveal man’s image in Naz Kakaees poetry especially in her divan titled as; howsfer 2017, which deals with man as essential subject but random one. The howser fold contains many images for man within and out the boundary of her family and what is worth to mention is that the positive images about man is more pervasive than the negative ones. Her poems reveal for us many sides of Naz personality, the female whom rejects constrains in all its forms. Naz was enabled by her artful skills to deliver her genuine feelings. The expressions that she has used were in harmony with the crises she had been through. This research is new about what it is present, for no research had dealt before with such subject exclusively.